Gendered institutions and women's political representation in Africa from participation to transformation - Diana Hj̜lund Madsen (London Zed Books, 2021)
During the course of the past three decades efforts of democratisation and institutional reforms have characterised the African continent, including demands for gender equality and women's political representation. As a result, some countries have introduced affirmative action measures, either in the aftermath of conflicts or as part of broader constitutional reforms, whereas others are falling behind this fast track to women's political representation. Utilising a range of case studies spanning both the success cases and the less successful cases from different regions, this work examines the uneven developments on the continent.
Includes Index
Keywords: Women -- Political activity -- Africa; Representative government and representation -- Africa; Equality -- Government policy -- Africa